Evaluasi dan Perbaikan Usability pada Dashboard PT.PLN (PERSERO) APD Jawa Timur Berorientasi Human Centered Design dan Key Performance Indicators - Gayuh Syahqila Ravdania; Ismiarta Aknuranda; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT.PLN APD Jatim is an organization of PT.PLN Distribution Jatim who served as a controller of distribution. This makes PLN APD Jatim has a lot of data to managed, so that need monitoring of the system such as the dashboard. The current dashboard is still less from interface side and does not match with needs of the user seen from Key Performance Indicators (KPI). Therefore, this research discusses about evaluation and usability improvement on dashboard PT.PLN (Persero) APD Jatim oriented human centered design and key performance indicators. Information gathering such as problem identification and usage context are obtained using interview method and system viewing for dig up information in more detail. Then for the framework of improvement, this research using Human Centered Design (HCD) because at each step of the research involves the user. The dashboard prototype was evaluated using a system usability survey and measured by System Usability Scale (SUS). SUS aims to generate the value of system usability. SUS is suitable for use because it can measure system using the minimal responden and can apply extensively. The evaluation results state that the solution design is good enough and according to needs of user so that no such repair.